The Contract – Main Source of Civil Obligations. Classification of Contracts - Ioana Nely MILITARU (CECCAR Business Review, 2022)

(untitled)
The objective of the article hereby is represented by the understanding of the notion of contract from the following perspectives: the contract is the main source of civil obligations and the contract is an agreement, a convention between parties, but also of the classification of contracts and of the practical importance of this classification.